Pernikahan Beda Agama Menurut Hukum Islam dan Hukum Positif - Rafa, Muhammad; Salwa, Cindy; Akbar, Ali (Yayasan Rahmat Islamiyah, 2024)
Marriage is an inner and outer bond between a man and a woman to create a happy life. As a pluralistic country, Indonesia has a diversity of religions and beliefs so that it indirectly has the potential for interfaith marriages or interfaith marriages. The marriage law in force in Indonesia also does not explicitly regulate interfaith marriages, giving rise to debate whether or not interfaith marriages are legal. This can cause various problems that arise in the community, especially couples who will carry out interfaith marriages. Therefore, this study aims to find out how interfaith marriages are regulated in the Marriage Law and what consequences will arise if interfaith marriages are still carried out by couples who are going to get married. This research uses library research type, which examines various documents related to research. The method used by the author is a normative juridical writing method using a statute approach. Furthermore, there are three legal materials used in this study, namely primary legal materials and secondary legal materials. The results of the research analysis show that marriage will cause many problems and legal consequences, including regarding family harmony, and the legal position of children if they have offspring from interfaith marriages. The Marriage Law should strictly regulate interfaith marriages so that there is no legal vacuum, and does not cause debate in addressing the issue of interfaith marriages.